The eye of the camera: photographic gaze and the question of visual violence - Ousmanova, Almira (Ukrainian Cultural Studies, 2024)
Background. This article examines the structure and forms of functioning of photography as a visual practice. In particular, a comparative analysis is conducted with the specifics of the organization and transformation of the practice of gaze in the logic of firearms. Methods. In this context, the author examines the syntagmatic relations of lexical units that give rise to subsequent practices and common metaphorical connections. A special place is occupied by the differentiation of lexical units of the metaphor of death in the context of the functioning of the practice and discourse of photography. In the article, the units of textual and linguistic analysis in the context of semiotics and tropology of visual culture are singled out in the methodological perspective. The purpose of the article is to analyze the logic of the correlation between the poetics and ethics of the visual practice of photography, in particular, to clarify the grounds for responsibility and legitimization of the photographer's view. Results. As a result, the foundations of the anthropological model of the "split subject" formed by the visual practice of photography are substantiated not only in the context of the opposition between the photographer and the photographed as inoforms of subject-object opposition, but also the degree of violence of photography as a cultural product, the consumption of which shapes the dynamics of the consumer's gaze and the basis for communication of the community as a consumer audience in this regard.Conclusions. As a result, the author comes to the conclusion that the improvement of photographic equipment technology expands the social circle of its consumers and, accordingly, the forms of their communication. The geometric growth of photography practices transforms the forms of social control, in particular, it technologies the practice of panopticism. The social pressure of the stranger's gaze generates "the inevitability of the modality of what is seen" (D. Joyce) and the permanence of the presence of the Other.
Keywords: visual violence; photographic Gaze; camera; ethics of the Gaze; split subject; death in photography; war